2016
DOI: 10.18632/oncotarget.11743
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factors regulate pluripotency factor expression by ZNF217- and ALKBH5-mediated modulation of RNA methylation in breast cancer cells

Abstract: Exposure of breast cancer cells to hypoxia increases the percentage of breast cancer stem cells (BCSCs), which are required for tumor initiation and metastasis, and this response is dependent on the activity of hypoxia-inducible factors (HIFs). We previously reported that exposure of breast cancer cells to hypoxia induces the ALKBH5-mediated demethylation of N6-methyladenosine (m6A) in NANOG mRNA leading to increased expression of NANOG, which is a pluripotency factor that promotes BCSC specification. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
201
3
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(216 citation statements)
references
References 47 publications
9
201
3
3
Order By: Relevance
“…Most recently, a growing number of studies have reported that methylases and demethylases of m 6 A are correlated with cancer (8,30,38,39). As METTL3 is the core component of m 6 A the methyltransferase complex, we wondered whether SUMOylation of METTL3 is connected with tumorigenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, a growing number of studies have reported that methylases and demethylases of m 6 A are correlated with cancer (8,30,38,39). As METTL3 is the core component of m 6 A the methyltransferase complex, we wondered whether SUMOylation of METTL3 is connected with tumorigenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Growing evidences have also revealed that key enzymes for m 6 A demethylation such as ALKBH5 (8,39) and FTO (38) have important regulatory roles in tumorigenesis. In this study, we found that the SUMO-site mutant METTL3-4KR repressed the anchor-independent growth and xenograft tumor growth in H1299 cells (Figure 5), possibly resulting from higher abundance of m 6 A methylation in mRNAs, when compared to those of METTL3-WT (Figures 4E, G and 6A–C).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, they showed that this response is dependent on the activity of hypoxia-inducible factors (HIFs) which induce the increase in cancer stem cell markers expression. They found that NANOG, SOX2, and OCT4 expression increased in all human breast cancer cells they analyzed in response to chemotherapy or hypoxia [77].…”
Section: Hifs Promote Stemness and Cancer Aggressivenessmentioning
confidence: 98%
“…A growing body of experimental evidence has indicated that cancerand metastasis-initiating cells with stem cell-like features typically display a higher resistance than the bulk mass of differentiated cancer cells to radiation therapy and chemotherapy, and thereby they can be responsible for disease relapse [76,77]. Cancer stem cells (CSC) are a small subpopulation of cells within various tumor types, which have the dual properties of self-renewal and differentiation by giving rise to both daughter cancer stem cells and bulk (non-stem) cancer cells, It has been demonstrated that CSCs are involved in initiating and sustaining tumor growth in many cancer types.…”
Section: Hifs Promote Stemness and Cancer Aggressivenessmentioning
confidence: 99%
See 1 more Smart Citation